THE ITALIAN JOB - Job N. 3, Lazy Sunday (2022) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
Lazy Sunday is the third work in THE ITALIAN JOB series. Started in 2014, straddling the distance between Italy and the United States, this series intends to highlight the hidden structures behind themes such as artistic legitimacy, virtuality, immaterial labour and 2.0 relationships between artists and curators. Lazy Sunday takes shape after an invitation to participate in a virtual residency within the spaces of the 12th Atelier of Casa degli Artisti in Milan. The artist accepts the invitation, overturning the assumptions of the residency: instead of participating at a distance, Vavarella transforms his point of view into an open space for the virtual participation of other people. The work consists of a 12-hour film made with a 360° camera and shot continuously on August 8 2021, on an ordinary day. Starting at 9:40 a.m., Emilio Vavarella filmed the events of one of his summer Sundays, recording his every activity, from waking up until the evening. The film has been shown in the space set up in the Casa degli Artisti, where visitors took on the point of view of the artist using a Virtual Reality headset.
Keywords: contemporary art; virtual reality; immersion; new media